Implementation Model of Environmental Accounting in Bumdes Pandawa Jaya to Realize Green Accounting - Ade Nurlaelatul Janah; Ana Sopanah; Hartini Prasetyaning Pawestri (Trescode Green Organization, 2024)
Environmental Accounting or Green Accounting is a term related to the inclusion of environmental costs in the accounting practices of companies or government agencies. The goal to be achieved in implementing environmental accounting is to carry out activities from the perspective of benefits and costs in order to increase the efficiency of waste management. These environmental costs are also integrated into business decision making and communicated to stakeholders, so that there is a need to allocate costs related to environmental conservation activities. This research aims to describe the implementation of Environmental Accounting at Bumdes Pandawa Jaya in Rengaspendawa Village which is implemented by Bumdes Pandawa Jaya. This research uses a qualitative method with a descriptive approach. Data collection techniques are carried out by means of observation, interviews and documentation. The research results show that BUMDES Pandawa Jaya has not implemented environmental accounting explicitly but only implemented environmental accounting implicitly through the waste management unit by incurring costs aimed at the environment. The implementation of environmental accounting is not yet optimal because costs incurred on the environment are not clearly detailed in the Bumdes financial reports and are still combined with other expenses. This is because Bumdes still uses a conventional or general accounting system which only classifies Bumdes performance income and expenditure, so that environmental costs are not visible.